Communication Basics in the Wildland-Urban Interface - Martha C. Monroe (EDIS)
FOR-112, a 5-page illustrated fact sheet by Martha C. Monroe, explores several strategies that natural resource professionals and extension agents can use to help make communication effective. Includes references. Published by the UF School of Forest Resources and Conservation, April 2007.